ANALISIS SOAL TIPE HIGH ORDER THINKING SKILLS (HOTS) PADA MATERI FPB KELAS IV - Lely Fitriyanti Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2022)
This research was motivated by the inability of students to understand or recognize the structure and composition of HOTS questions in mathematics. One of the efforts to overcome the problem of low learning achievement and students' thinking skills is to carry out daily assessments which are benchmarks, so there should be a question component by measuring higher-order thinking skills.The purpose of the study was to describe the quality of the odd semester daily assessment questions on the fourth grade FPB material at Elementary School. This type of research is descriptive and uses a qualitative approach. The daily assessment HOTS questions were analyzed by the researcher. The data analysis in this research is to analyze the quality of the questions in the HOTS and LOTS categories, analyze the questions and analyze the characteristics of critical thinking skills, creative thinking skills and problem solving abilities. Based on the results of the study, it showed that the quality of the HOTS questions on the daily assessment with a percentage of 60%.